A COMPARISON OF CHILI PRICE VOLATILITY IN CRUSHING PROVINCE OF INDONESIA - hariz wibowo; Rihan Ifebri; Ariffatchur Fauzi (Journal of Agri Socio Economics and Business, 2023)
The price of chili commodity can be used as the main indicator of inflation because it can respond quickly, especially to changes in demand and economic changes. Production fluctuations and consumption fluctuations have an impact on price fluctuations. Prediction of time series data using the ARIMA model approach has good performance for predicting chili prices in the future. Crucial province is the province that has big impact such as the province with the highest production, or the province with the highest consumption or the province with the gaps such as Jawa barat and Banten province. The purpose of this research is to create a time series model to predict chili prices in Jawa barat and Banten provinces and to measure and compare the level of volatility in chili prices in Jawa barat and Banten provinces. The best ARIMA model for chili price data in Jawa Barat and Banten Provinces is the ARIMA model (0,1,1). The results of chili forecast data in the provinces of Jawa Barat and Banten using the ARIMA model show relatively stable prices. The volatility of chili prices in Jawa Barat province is 19.68%. Chili price volatility in Banten province is 20.49%. This shows that the volatility level of chili prices in Jawa Barat province is relatively lower than in Banten province, although it is relatively the same and is still under control. This is confirmed by the result that the model has no ARCH effect.